Relationship Between Respiratory Enzymes and Survival of Escherichia coli Under Starvation Stress in Lake Water - Özkanca, R.; Flint, K.P. (Blackwell Publishing Ltd, 1997)
Survival, electron transport system (ETS) activity and the activity of NADH and succinate dehydrogenase of Escherichia coli ML30 were studied under starvation stress at different temperatures in a filtered-autoclaved lake water microcosm. ETS activity in E. coli declined rapidly at 30°C but more slowly at 4°and 15°C over a 20 d starvation period. The decrease in ETS activity in E. coli only started after 6 d of incubation at 4°C and 15°C. Viability of E. coli, as determined by plate counts, declined faster at 37°C than at the other temperatures and remained highest at 4°C in filtered-autoclaved lake water. There was also a significant cell size reduction at 37°C in filtered-autoclaved lake water but not at 4°C. ETS activity after up to 16 d of starvation increased after the addition of nutrient broth to the filtered-autoclaved lake water at 15°C and 30°C suggesting that cells were still able to respond to nutrients, even after prolonged starvation. The response to the addition of nutrient broth, however, declined with the length of the starvation period. The activity of both succinate and NADH dehydrogenase declined over a 13 d starvation period. The loss of activity was fastest at 37°C compared to lower incubation temperatures but even at 4°C, a significant proportion of the activity was lost over the 13 d period.